A Network-Based Examination of the Longitudinal Association Between Psychopathy and Offending Versatility - McCuish, Evan (Journal of quantitative criminology, 2021)
Objectives Concerns about the value of features of psychopathy to explanations of offending may be driven by challenges with testing this relationship as opposed to the construct’s limited predictive validity. The current study introduced psychopathology network modeling as an analytic strategy capable of addressing these challenges through a more nuanced description of the structural and statistical association between features of psychopathy and offending. To provide more direct implications for criminological theory and research, this included examining whether within-individual changes in features of psychopathy were associated with within-individual change in offending. Methods Data on male and female young offenders from the Pathways to Desistance Study ( n = 1354) were used to examine the association between features of psychopathy and offending versatility, as measured by the Youth Psychopathic Traits Inventory and the Self Report of Offending scale, respectively. Three network structures were modeled that separated the variance in the relationship between features of psychopathy and offending into between-subjects and within-individual networks. Results Between-subjects and within-individual analyses indicated that interpersonal and affective features of psychopathy were positively associated with offending versatility. The network approach indicated that remorselessness and manipulativeness were central features of psychopathy that were also associated with offending versatility. Remorselessness in particular helped bridge together conceptually distinct features of psychopathy. Conclusions Psychopathology network modeling illustrated the value of features of psychopathy to mainstream criminological theory and research. These features included interpersonal and affective deficits, which previously were identified as poor predictors of offending outcomes.